Efficacy of conventional and digital radiographic imaging methods for diagnosis of simulated external root resorption Eficácia dos métodos radiográficos convencional e digital no diagnóstico de reabsorções radiculares simuladas - Vânia Portela Ditzel Westphalen; Ivaldo Gomes de Moraes; Fernando Henrique Westphalen (University of São Paulo, 2004)
This in vitro study evaluated and compared the efficacy of conventional (Kodak F-speed (Insight), Kodak) and a digital (DRS Gnatus System, Gnatus) radiographic imaging for diagnosis of simulated external root resorption cavities. Human mandibles containing teeth were covered with bovine muscle slices in order to simulate the soft tissues. Nine teeth out of each group of teeth were investigated. Initially, three periapical radiographs of each tooth were taken using a tube shift technique with mesial and distal angulations in both methods. All teeth were subsequently extracted and had 0.7 and 1.0-mm deep cavities prepared on their buccal, mesial and distal surfaces at the cervical, middle and apical thirds. Steel cylinder burs (DORMER® - HSS) with 0.7 and 1.0-mm diameter were used. Each tooth was replaced on its socket and new radiographs were taken. Three examiners, an endodontist (1), a radiologist (2) and a general dentist (3), evaluated the images. Results were compared by z-test and showed a higher number of cavities detected by the digital method compared to the conventional, regardless of the deepness of the cavity. In decreasing order, examiners 2, 3 and 1 exhibited different potentials of detection of cavities with the conventional method. Examiners 1 and 3 exhibited superior potential than examiner 2 for detection of cavities of different sizes with the digital method. O presente estudo visou avaliar e comparar, in vitro, a eficácia dos métodos radiográficos convencional (filmes de grupos de sensibilidade E/F Kodak Insight) e digital (Sistema Gnatus DRS), no diagnóstico de cavidades simulando reabsorções radiculares externas, em dentes contidos em mandíbulas humanas secas com músculo bovino simulando o tecido mole. As variáveis consideradas foram: tamanhos das cavidades e examinadores envolvidos. Foram utilizadas nove unidades de cada grupo dentário, incisivos (central e lateral), caninos, pré-molares e molares, sem lesões periapicais, as quais foram radiografadas inicialmente, em três tomadas radiográficas periapicais (orto, mesio e distorradial) pelos métodos radiográficos convencional e digital. Extraíram-se os dentes com o auxílio de fórceps e as cavidades de reabsorção foram confeccionadas com brocas cilíndricas DORMER® - HSS - Aço rápido, de 0,7 e 1,0 mm de diâmetro, nas profundidades 0,7 e 1,0 mm, para simular cavidades pequenas e médias, respectivamente, distribuídas nos terços radiculares cervical, médio e apical e nas faces vestibular, mesial e distal. Após a realização das cavidades os dentes eram reposicionados nos alvéolos e então, radiografados novamente pelos métodos convencional e digital, sendo esses passos comuns a ambos os diâmetros e profundidades das cavidades. As radiografias convencionais e digitais foram avaliadas por três cirurgiões-dentistas, sendo um radiologista, um endodontista e um clínico geral. Os resultados da investigação mostraram que, pelo método radiográfico digital o número de cavidades observadas foi maior do que pelo convencional, tanto para as cavidades pequenas (p<0,05), quanto para as médias (p<0,05).